How the Commissioners Explained Treaty Number Nine to the Ojibway and Cree in 1905 - Long, John (Ontario History)

(untitled) (The Ontario Historical Society, 2006)
How did government representatives explain Treaty No. 9 to the Ojibway and Cree of northern Ontario during the summer of 1905? The written treaty on which the commissioners obtained the marks and signatures of certain Ojibway and Cree, is a legal instrument which sought to remove the impediment of “Indian title” to the land, freeing it for state projects, claiming its indigenous inhabitants as subjects, extending to them some of the responsibilities and benefits and symbols of citizenship, and granting them certain gifts. The commissioners’ own records, however, indicate that treaty signing was a very different transaction. Most of the actual terms of the written treaty were not explained to the Ojibway and Cree, who gave their consent only to the commissioners’ oral explanations. For them, the treaty was an oral covenant acknowledging their continuing need to use the land, and providing them with promises of assistance and protection.